Restricted Proliferation During Neurogenesis Contributes to Regionalisation of the Amphioxus Nervous System - Gattoni, Giacomo; Andrews, Toby G. R.; Benito-Gutiérrez, Èlia (Frontiers in Neuroscience, 2022)
The central nervous system of the cephalochordate amphioxus consists of a dorsal neural tube with an anterior brain. Two decades of gene expression analyses in developing amphioxus embryos have shown that, despite apparent morphological simplicity, the amphioxus neural tube is highly regionalised at the molecular level. However, little is known about the morphogenetic mechanisms regulating the spatiotemporal emergence of cell types at distinct sites of the neural axis and how their arrangements contribute to the overall neural architecture. In vertebrates, proliferation is key to provide appropriate cell numbers of specific types to particular areas of the nervous system as development proceeds, but in amphioxus proliferation has never been studied at this level of detail, nor in the specific context of neurogenesis. Here, we describe the dynamics of cell division during the formation of the central nervous system in amphioxus embryos, and identify specific regions of the nervous system that depend on proliferation of neuronal precursors at precise time-points for their maturation. By labelling proliferating cells in vivo at specific time points in development, and inhibiting cell division during neurulation, we demonstrate that localised proliferation in the anterior cerebral vesicle is required to establish the full cell type repertoire of the frontal eye complex and the putative hypothalamic region of the amphioxus brain, while posterior proliferating progenitors, which were found here to derive from the dorsal lip of the blastopore, contribute to elongation of the caudal floor plate. Between these proliferative domains, we find that trunk nervous system differentiation is independent from cell division, in which proliferation decreases during neurulation and resumes at the early larval stage. Taken together, our results highlight the importance of proliferation as a tightly controlled mechanism for shaping and regionalising the amphioxus neural axis during development, by addition of new cells fated to particular types, or by influencing tissue geometry.